None of Our Wars Ended Where They Began - Tabora, Brylle B. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
These poems were written shortly after the recent national elections that saw the victory of the late dictator’s son. Like most disaffected voters, bogged down by the upsetting news, I could not bring myself to accept the election results that would herald another Marcos in power and allow for a continuation of the Duterte administration known for its bloody war on drugs. So, these are poems of rage and protest—an anthem railing against a government marked by political dynasties, traditional patronage, deepseated oppression, democratization of disinformation, and human rights abuses. Never again!